Pemanfaatan Sungai Konawe Eha sebagai Sumber Ekonomi Masyarakat Desa Puusangi, Kecamatan Anggalomoare, Kabupaten Konawe - Moita, Muhammad Ikbal; Winesty Sofyani, Wa Ode; Raemom, Raemon (JURNAL KABANTI: Kerabat Antropologi, 2025)
The Konawe Eha River plays an important role in the lives of the people of Puusangi Village, Anggalomoare District, Konawe Regency, as a vital economic resource. This research aims to analyze the utilization of the Konawe Eha River as an economic resource for the community in Puusangi Village, Anggalomoare District, Konawe Regency. This study employs a qualitative approach with ethnographic methods to collect relevant data. The research results show that the people of Puusangi Village utilize the Konawe Eha River for three main activities: sand mining, Pincara ferry services, and searching for pokea clams. Sand mining has become the main source of income due to high demand and stable sand prices, although it negatively impacts the environment, such as soil erosion and a decline in fish populations. The Pincara ferry service facilitates mobility, especially for miners, while the search for pokea shells provides additional income and is part of the local culinary tradition. This river has become the main economic source because it provides abundant resources and more lucrative job opportunities compared to traditional sectors like agriculture. However, the impact is environmental damage and decreased attention to the agricultural sector, which is starting to be neglected.